UNUSED LABOR RESOURCES AND BARRIERS TO TAKING UP EMPLOYMENT BY PEOPLE WITH DISABILITIES - Stolarczyk, Paulina (Acta Scientiarum Polonorum. Oeconomia, 2023)
Aim: The study concerns unused labor resources such as people with disabilities. The aim of the article is to present the situation of people with disabilities in the labor market and barriers to taking up employment. People with disabilities are in a more difficult situation in the labor market than non-disabled people, which is confirmed by the values of labor market measures. The barriers that make it difficult and sometimes impossible to find a job have been identified and characterized. Methods: The article uses secondary and primary data. Primary data came from research carried out in the Mazowieckie Voivodeship. The participants of the study were people with disabilities of working age. The article uses descriptive statistics methods. The results were presented in tabular and graphic form. Results: The most important findings include the observation that the most common reason for people with disabilities not taking up work is poor health, which makes it impossible to take up employment. The second main reason is the fear and reluctance to lose the disability benefit, e.g., disability pension. An important finding is also that people with a minor disability have far fewer barriers than people with a moderate disability. Conclusions: The hypothesis that people with disabilities are a resource of unused labor due to external factors independent of themselves, such as the lack of job offers and the reluctance of employers to employ people with disabilities, has been positively verified. People with disabilities are unused labor resources that need to be activated.